2016
DOI: 10.1002/ange.201510724
|View full text |Cite
|
Sign up to set email alerts
|

CuSO4/H2O2‐Induced Rapid Deposition of Polydopamine Coatings with High Uniformity and Enhanced Stability

Abstract: Mussel-inspired polydopamine (PDA) deposition offers ap romising route to fabricate multifunctional coatings for various materials.H owever,P DA deposition is generally at ime-consuming process,a nd PDAc oatings are unstable in acidic and alkaline media, as well as in polar organic solvents. We report astrategy to realize the rapid deposition of PDAby using CuSO 4 /H 2 O 2 as atrigger.Compared to the conventional processes,o ur strategy shows the fastest deposition rate reported to date,and the PDAcoatings exh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
109
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 151 publications
(114 citation statements)
references
References 38 publications
5
109
0
Order By: Relevance
“…18 To understand the role of Cu 2+ in the polymerization of DOPA solution, UV-VIS was used to monitor the formation of PDA having a characteristic absorbance peak at 420 nm. 16 When DOPA solution was acidic at pH 4.5, as shown in Figure S5, there was no absorbance detected at 420 nm and no color change observed in air with the absence of Cu 2+ , which has been reported that DOPA could not selfpolymerize at acidic condition. However, the presence of Cu 2+ made the DOPA solution at pH 4.5 have color change rapidly from pale brown to dark brown, and have increasing strong absorbance at 420 nm in 40 minutes, indicating Cu 2+ initiated the polymerization of DOPA at pH 4.5.…”
Section: Zongyao Zhou 12mentioning
confidence: 74%
See 2 more Smart Citations
“…18 To understand the role of Cu 2+ in the polymerization of DOPA solution, UV-VIS was used to monitor the formation of PDA having a characteristic absorbance peak at 420 nm. 16 When DOPA solution was acidic at pH 4.5, as shown in Figure S5, there was no absorbance detected at 420 nm and no color change observed in air with the absence of Cu 2+ , which has been reported that DOPA could not selfpolymerize at acidic condition. However, the presence of Cu 2+ made the DOPA solution at pH 4.5 have color change rapidly from pale brown to dark brown, and have increasing strong absorbance at 420 nm in 40 minutes, indicating Cu 2+ initiated the polymerization of DOPA at pH 4.5.…”
Section: Zongyao Zhou 12mentioning
confidence: 74%
“…The molar fractions of copper element on the Psf, TFC-FO polyamide layer, and PVDF were determined to be 1.4%, 2.33% and 1.36%, respectively, which are very close to the reported 2.41% on other substrates. 16 In addition, the molar fractions of nitrogen elements were high up to 7.26%, and 5.02% on the Psf and PVDF membrane surfaces, respectively, indicating the thick coatings of PDA formed. The forms of the immobilized copper were also analyzed to see the typical BE peak of Cu 2+ at 934.4 eV shown in Figure 2C and another characteristic Cu 2+ satellite peaks around 963 eV and 943 eV shown in Figure 2B.…”
Section: Zongyao Zhou 12mentioning
confidence: 92%
See 1 more Smart Citation
“…And Cu 2+ ions can serve as a cross-linker via chelation with PDA, which can also improve the stability and antibacterial performance of the coatings. However, it should be noted that high concentration of H 2 O 2 in the absence of CuSO 4 can suppress the deposition of PDA, which may be ascribed to the fact that H 2 O 2 is an intermediate product of DA polymerization, and its high concentration could disturb the internal structure of PDA [23,24]. On the other hand, Ponzio et al [25] compared the effects of three different oxidants (APS, sodium periodate, and copper sulfate) on PDA deposition.…”
Section: Recent Advances In Mussel-inspired Surface Chemistrymentioning
confidence: 99%
“…The surface morphology of PDA coatings showed no evident differences between the APS-and pH-induced deposition. Furthermore, Zhang et al [23] utilized CuSO 4 /H 2 O 2 as a trigger to accelerate DA polymerization. In this case, reactive oxygen species can facilitate the covalent reaction among PDA molecules, and enhance the stability of PDA coatings.…”
Section: Recent Advances In Mussel-inspired Surface Chemistrymentioning
confidence: 99%